305. Cholecystitis as a Possible Immunologic Consequence of COVID-19; Case Series from a Large Healthcare System. (4th December 2021) - Jacobs, Anna; Polk, Christopher; Sampson, Mindy; Kooken, Banks; Ludden, Thomas; Passaretti, Catherine; Passaretti, Catherine; Leonard, Michael
Abstract: Background: Gastrointestinal manifestations are commonly seen in COVID-19 disease with up to 50% of patients reporting nausea or diarrhea. Cholecystitis has been described in rare cases related to COVID-19, possibly in consequence of immune activation, but biliary disease from SARS-CoV-2 infection is not well described. We examined a case series of patients with both COVID-19 and cholecystitis at our institution. Methods: We performed a retrospective chart review of all patients with a diagnosis of cholecystitis within 3 months of SARS-CoV-2 infection; looking at clinical, laboratory, and radiographic characteristics of this population. Results: 30 individuals were identified with a diagnosis of cholecystitis within 3 months of diagnosis of SARS-CoV-2 infection. Most patients presenting with cholecystitis were female and obese (see Table 1). 14 individuals were diagnosed with SARS-CoV-2 infection during the same presentation as their cholecystitis diagnosis, usually as part of pre-operative screening. Of 16 individuals diagnosed with SARS-CoV-2 prior to their cholecystitis presentation, a mean of 24 and 17 days elapsed between SARS-CoV-2 infection and cholecystitis symptom onset and radiographic diagnosis, respectively (see Figure 1). Most of these patients had mild respiratory disease, with only 9 developing an oxygen requirement, and only 3 requiring mechanical ventilation. While 17 patients were treated surgically for their cholecystitis, this did not appear to impact symptom resolution. Table 1. Patient Characteristics Figure 1. Time between COVID-19 and Cholecystitis Conclusion: Cholecystitis may be an uncommon complication of COVID-19 disease. Cholecystitis may manifest most often 2-4 weeks following SARS-CoV-2 infection. This timing is similar to that in Multisystem Inflammatory Syndrome following SARS-CoV-2 infection and given similarities in timing to we hypothesize that cholecystitis in our patients could be driven by immune activation. Disclosures: Christopher Polk, MD, Atea (Research Grant or Support)Gilead (Advisor or Review Panel member, Research Grant or Support)Humanigen (Research Grant or Support)Regeneron (Research Grant or Support) Mindy Sampson, MD, Regeneron (Grant/Research Support) Catherine Passaretti, MD, Nothing to disclose